Assessment of the bachelor of science in midwifery program of University of Eastern Pangasinan : basis for a proposed development plan - Ganzon, Glenda B. (Panpacific University : [s.n.], 2018)
To reduce maternal mortality rate is one of the Millennium Development Goals (MDG5). Improving Maternal and Newborn Health and reducing mortality and morbidity requires the strengthening of health systems. Positive efforts to improve quality education have been made by many partners under the leadership of International Confederation of Midwives (ICM), International Federation of Gynecologists and Obstetrics (FIGO) and Independent Practice association (IPA), and through United Nations agencies, donors and foundations, and major international and national NGOs (WHO 2015).In response to these gaps and barriers, Bharj et al (2016) have set out a new agenda to Improve the quality of education. Global Standards for Midwifery Education is one of the essential pillars of ICM's efforts to strengthen midwifery worldwide by preparing fully qualified midwives to provide health services for women, newborns, and childbearing families. Quality assurance is the expression that is new in education and has quickly become very important (Allais, 2009). This created a profound effect upon the educational landscape and has transformed the view of quality in higher education. With the foregoing ideas the researcher had contemplated, a study which aimed to determine the status of Bachelor of Science in Midwifery Program was made. Furthermore, the result of the study will serve as a basis to develop the ten areas of the program and comply with the lapses. Development plan will serve as a guide of the Lapses. Development plan will serve as a guide of the College of Midwifery towards the realization of its goal and will serve as a basis in decision making of what the College of Midwifery aspires to achieve. 8.2 Dummary of Findings The following is the summary of the salient findings of the study: 1. Community Extension Program was perceived to be the area with the highest average. Involvement in the community is a basic aspect of the program, most especially in a developing country like the philippines, where community Involvement may be equated to the total efforts whereby the college or university relates itself to national, regional and local imperatives of development. On the other hand, Student Development Services was noted to be the area with the lowest average. This area is the integration of academic learnings and its objective is to develop personal and individual growth to prepare the students for the challenges of tomorrow. More so, all of the ten areas were revealed to have rated under the point value of three or "good" descriptive equivalent which means that the program had complied with the criterion under the ten areas. 2. There are eight factors that affect the status of B.S. Midwifery program cited by the respondents. One was the "scholarship programs" offered by the 8.5. Midwifery noted to have cited by most of them. In addition, the accessible location of the UEP and qualified faculty members who are professionally competent being the second and the third most cited factor. The teaching role of faculty members reflects their centrality in addressing the primary educational mission of the school. Another is the "employment opportunities of the graduates." UEP owns a Birthing Home that serves as a clinical setting for clinical experience of B.S. Midwifery students. Graduates of UEP have a high chance of being employed. "Passing percentage of licensure examination for midwives" is also one of the factors that affect the status of the program. The result of licensure examination signifies the quality of education UEP Midwifery program has to offer. In addition, "number of enrollees" and "linkages with government and non-government organization and agencies" and "resources adequacy" are the least among the factors. This is due to UEP as a local university wherein Rural Health Units and Barangay Health facilities in Binalonan.
References: pages 145-151.
CHED-La Union
Keywords: Midwifery